KETERAMPILAN BELA DIRI ANGGAR - Ika Kusumasari (Universitas Negeri Medan, 2014)
The objective or research is to determine the relationship between leg length (X1) and speed of reaction (X2) with lunge accuracy of fencing skill. This research was conducted at IKASI Banten 2008, with samples of 20 respondents selected by total sampling.The result of this research are as follows. First, there is a positive correlation between leg length toward lunge accuracy of fencing skill. The linear regression is express through. The correlation coefficient 0.47.it’s mean the contribution of leg length toward lunge accuracy of fencing skill is 22.09 %. Second, there is a positive correlation between speed of reaction toward lunge accuracy of fencing skill. The linearregression is express through . The correlation coefficient 0.55.it’s mean the contribution of leg length toward lunge accuracy of fencing skill is 30.25 %. Third, there is a positive correlation between leg length and speed of reaction toward lunge accuracy of fencing skill. The linear regression is expree through . The correlation coefficient 0.61.it’s mean the contribution of leg length toward lunge accuracy of fencing skill is 37.21 %.